Mediating Factors Explaining the Association Between Sexual Minority Status and Dating Violence - Martin-Storey, Alexa (Journal of interpersonal violence, 2021)
Dating violence presents a serious threat for individual health and well-being. A growing body of literature suggests that starting in adolescence, individuals with sexual minority identities (e.g., individuals who identify as gay, lesbian, or bisexual) may be at an increased risk for dating violence compared with heterosexuals. Research has not, however, identified the mechanisms that explain this vulnerability. Using a diverse sample of young adults (n = 2,474), the current study explored how minority stress theory, revictimization theory, sex of sexual partners, and risky sexual behavior explained differences in dating violence between sexual minority and heterosexual young adults. Initial analyses suggested higher rates of dating violence among individuals who identified as bisexual, and individuals who identified as gay or lesbian when compared with heterosexuals, and further found that these associations failed to differ across gender. When mediating and control variables were included in the analyses, however, the association between both sexual minority identities and higher levels of dating violence became nonsignificant. Of particular interest was the role of discrimination, which mediated the association between bisexual identity and dating violence. Other factors, including sex and number of sexual partners, alcohol use, and childhood maltreatment, were associated with higher rates of dating violence but did not significantly explain vulnerability among sexual minority individuals compared with their heterosexual peers. These findings suggest the importance of minority stress theory in explaining vulnerability to dating violence victimization among bisexuals in particular, and generally support the importance of sexual-minority specific variables in understanding risk for dating violence within this vulnerable population.